Spectroscopic investigation, thermal behavior, catalytic reduction, biological and computational studies of novel four transition metal complexes based on 5-methylthiophene Schiff base type - Doaa A. Nassar; Omyma A.M. Ali; Mohamed R. Shehata; Abeer S.S. Sayed (Heliyon, 2023)
Four new complexes prepared from 5-Methyl-2-carboxaldehyde-thiophene and 2,6-pyridinediamine with cobalt, nickel, copper and cadmium ions have been synthesized because of the significance of these complexes in pharmacological research and catalytic reduction. The prepared compounds were characterized using elemental analysis, mass, UV–visible, NMR and FTIR spectroscopy, as well as molar conductance, magnetic susceptibility measurements, fluorescence properties and TGA analysis. The stoichiometry mode was confirmed as 1:1 (metal: ligand) for Co, Ni and Cu complexes and 1:2 (metal: ligand) for Cd complex according to the results of the elemental and spectral studies. Furthermore, the thermal stability and luminescence properties of complexes have been studied. Thermal studies confirmed the presence of water molecules. The thermodynamic properties of the complexes were measured via the Coats-Redfern procedure. The geometric structures of the complexes were found to be octahedral around the metal ions. The optical energy gaps (Eopt) vary between 2.92 and 3.71 eV indicating that these compounds can be used as selective absorbing solar energy in photovoltaic applications. In the presence of NaBH4, the greatest reduction efficiency for the conversion of 2-NP to 2-AP was discovered to be 73–91% within 15–25 min. In vitro, high antifungal and antibacterial activity was shown by complexes than the ligand alone. The Cd(II) complex was shown to have greater activity than all of the examined microorganisms when compared to the reference drug in addition it had 4.94 μg/ml minimal inhibitory concentration against “S. aureus”, “B. subtilis”, and “E. coli”. The bond angles, bond lengths, and quantum chemical factors of the ligand and complexes were shown in the molecular modeling using the DFT approach. The studied compounds' binding modes were confirmed using the Gaussian 09 program.